Analysis of eddy currents induced by transverse and longitudinal gradient coils in different tungsten collimators geometries for SPECT/MRI integration. Issue 6 (26th November 2014) - Samoudi, Amine M.; Van Audenhaege, Karen; Vermeeren, Günter; Poole, Michael; Tanghe, Emmeric; Martens, Luc; Van Holen, Roel; Joseph, Wout
Abstract : Purpose: We investigated the temporal variation of the induced magnetic field due to the transverse and the longitudinal gradient coils in tungsten collimators arranged in hexagonal and pentagonal geometries with and without gaps between the collimators. Methods: We modeled x‐, y‐, and z‐gradient coils and different arrangements of single‐photon emission computed tomography (SPECT) collimators using FEKO, a three‐dimensional electromagnetic simulation tool. A time analysis approach was used to generate the pulsed magnetic field gradient. The approach was validated with measurements using a 7T MRI scanner. Results: Simulations showed an induced magnetic field representing 4.66% and 0.87% of the applied gradient field (gradient strength = 500 mT/m) for longitudinal and transverse gradient coils, respectively. These values can be reduced by 75% by adding gaps between the collimators for the pentagonal arrangement, bringing the maximum induced magnetic field to less than 2% of the applied gradient for all of the gradient coils. Conclusion: Characterization of the maximum induced magnetic field shows that by adding gaps between the collimators for an integrated SPECT/MRI system, eddy currents can be corrected by the MRI system to avoid artifact. The numerical model was validated and was proposed as a tool for studying the effect of a SPECT collimator within the MRI gradient coils. Magn Reson Med 74:1780–1789, 2015. © 2014 Wiley Periodicals, Inc.